Financial Performance of Sharia Governments Banks And Regional Sharia Government Banks - Julianto Hutasuhut; Henny Andriyani Wirananda; Ardhansyah Putra Harahap (University of Merdeka Malang, 2023)
The purpose of research to find out and analyze if there is a significant diferences between ROA, ROE, CAR and NPL at Bank Syariah Indonesia (BSI) and Bank Sumut Syariah at covid-19 pandemic era. The research is quantitative study. As for the research instrument used in collecting the data namely financial reports in the form of a balance sheet at BSI and Bank Sumut Syariah for four years from 2018- 2021. The population used in this research is the annual financial statement at BSI and Bank Sumut Syariah. The data analysis technique used is the t-test. The result of analysis used to t-test sampling of CAR and ROE showed that there is no the diversity of significant financial performance between BSI with Bank Sumut Syariah furthermore in ROA variable and NPL showed there is the diversity of significant financial performance between BSI and Bank Sumut Syariah.